HUBUNGAN KADAR D-DIMER DENGAN DERAJAT KEPARAHAN PENYAKIT DAN ANGKA KEMATIAN PASIEN CORONAVIRUS DISEASE 2019 - Trisuliandre, Muhammad Rizki; Herman, Deddy; Yulistini, Yulistini; Efrida, Efrida; Meinapuri, Malinda; Hasmiwati, Hasmiwati (EMPIRIS : Jurnal Sains, Teknologi dan Kesehatan, 2025)
Objective: This study aims to determine the relationship between D-dimer levels and the severity of the disease and the mortality rate of Coronavirus Disease 2019 patients treated at Dr. M. Djamil Padang General Hospital for the period June-August 2021. Method: This type of research is observational analytic using a retrospective cohort study design by taking a sample of 75 people through medical record data. Results: Most of the characteristics of the Coronavirus Disease 2019  patients were found in the age group of 56-65 years, male sex, most of them had an increased D-dimer value, and most of the patients did not die. This study found that there is a relationship between D-dimer levels and the severity of the disease and the mortality rate of Coronavirus Disease 2019 patients. Based on the Odd Ratio value obtained of 2.04 (1.53-2.71), it can be interpreted that people who have D -dimer increases have a risk of dying 2 times. Conclusion: There is a relationship between D-dimer levels and the severity of the disease and the mortality rate of 2019 Coronavirus Disease patients at Dr. M. Djamil Padang for the June-August 2021 period.